Photoconductivity as loss mechanism in organic solar cells - Tress, W; Leo, K; Riede, M (Wiley, 2013)
We observe that the reverse current under illumination in solar cells containing C60 and ZnPc is dominated by a photoshunt. This shunt, not present in the dark, causes a linear current-voltage relation under illumination showing no saturation. Although observable in bulk heterojunctions, this effect is more pronounced in the presence of a pristine C60 layer. An internal quantum efficiency larger than unity under an applied negative voltage and in the spectral range where C60 absorbs identifies charges which are injected in addition to those photogenerated. The photoshunt is also present in the power-generating region and represents a loss mechanism limiting the fill factor in particular for flat heterojunction devices. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.